2018
DOI: 10.1182/bloodadvances.2017014175
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of a multivalent WT1 peptide vaccine (galinpepimut-S) in acute myeloid leukemia

Abstract: Key Points A heteroclitic WT1 peptide vaccine is well tolerated and induces immunologic responses in most acute myeloid leukemia patients post-CR1. Median overall survival for the group of patients vaccinated was not reached but is poised to reach or exceed 67.6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 44 publications
1
91
0
Order By: Relevance
“…Another example is between WT1 and HLA-B . The WT1 protein has been chosen as an immunologic target by a National Cancer Institute initiative [46], and this year, a phase 2 clinical trial showed a WT1 vaccine that is effective in Acute Myeloid Leukemia with predicted binding on HLA-B*15:01, HLA-B*39:01, HLA-B*07:02, and HLA-B*08, HLA-B27:05 in addition to HLA-A*02 [47]. These MeTeOR predictions suggests that further investigation is warranted and highlights the ability of the network to suggest complex gene–disease–gene relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Another example is between WT1 and HLA-B . The WT1 protein has been chosen as an immunologic target by a National Cancer Institute initiative [46], and this year, a phase 2 clinical trial showed a WT1 vaccine that is effective in Acute Myeloid Leukemia with predicted binding on HLA-B*15:01, HLA-B*39:01, HLA-B*07:02, and HLA-B*08, HLA-B27:05 in addition to HLA-A*02 [47]. These MeTeOR predictions suggests that further investigation is warranted and highlights the ability of the network to suggest complex gene–disease–gene relationships.…”
Section: Resultsmentioning
confidence: 99%
“…antigens such as SLAMF7, CD38, CD74, or CD138 39 , providing naturally processed HLA-presented ligands derived from intracellular domains of established membrane-bound tumor-associated antigens. Such HLA ligands represent promising targets for (i) low side effect single agent vaccine approaches in elderly patients or early disease states 21,28,40 , (ii) TCR-engineered T cells 41 , (iii) antibody-based approaches 42 , or (iv) novel approaches combining HLA-dependent and -independent antigens and treatments 43 . In addition, such T-cell epitopes can be used for the assessment and monitoring of T-cell responses following various types of antigen-specific, or as in this example BCMA-specific, immunotherapy approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide vaccine is often synthetic and mimics naturally occurring proteins from pathogens and these peptides based vaccine have shown promising successful results in the past for disease like malaria, dengue, multiple sclerosis, influenza. Besides of these diseases, peptide based vaccines have also been developed against several types of cancer like colorectal cancer, myeloid leukaemia and gastric cancer (47),(48),(49). The identification and design of immunogenic peptides (epitopes) is expensive as well as time consuming.…”
Section: Discussionmentioning
confidence: 99%